A Theoretical Analysis of Literature of Accelerating and Anisotropic Cosmological Models in Certain Modified Theories of Gravitation (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Cosmology is the scientific study of the relationship between space and time, with an emphasis on the origin, structure, and nature of the universe. The universe has evolved through numerous stages, revealing its entire complexity. To fully fathom the nature of our world, we must first understand its origins, evolution, and ultimate fate. The process of creating mathematical models of the universe. Einstein's theory of general relativity explains the force of gravity, whilst other theories investigate gravitational consequences in a Bianchi universe. The class of cosmological models that are intrinsically homogeneous but not isotropic on spatial slices is named after Luigi Bianchi, a mathematician who categorised these spaces in three dimensions. After doing theoretical research, it is determined that infinitesimally tiny singularities do not entirely meet the energy density constraint, and instead, a rebound occurs in place of the universe's original singularity. The solutions have densities that exceed the maximum density and are effective for connecting anisotropic solutions, even in the absence of shear at the bounce.A cosmological model of the Bianchi type II that is both spatially homogeneous and totally anisotropic. In the context of general relativity, the model is filled with pressure-less matter and anisotropic modified Ricci dark energy, as well as an attracting massive scalar field.A solution to Einstein's field equations using Bianchi type II space-time, which provides a logical explanation for the inflationary state and isotropy in the absence of singularities or particle boundaries.